Citizen observatories: concept, opportunities and communication with citizens in the first EU experience - Montargil, Filipe (2017)
This chapter discusses the emerging concept of Citizen observatories (COs), explores the opportunities it represents for public authorities to go beyond incremental bureaucratic innovation and presents the ﬁrst generation of European-funded experiences, held between 2012 and 2016. The concept of CO implies, according to the existing deﬁnitions, an open and shared information system dedicated to the collection of data on the environment and natural resources, using ICT, and the volunteer participation of individuals in data collection. The EU has adopted a more speciﬁc concept of CO in the projects funded, so that the resulting information complements existing earth observation systems (including the European Copernicus satellite programme). In the 2012–2016 period ﬁve CO projects have been funded by the EU, covering different areas: natural waters monitoring, odour monitoring, air quality monitoring, ﬂood risk management and a platform for citizen science surveys. These COs allowed to develop and test the concept’s implementation, although the societal impact is still very limited, involving a reduced number of users. These projects have, however, established a very valuable set of resources, knowledge and expertise. This is an emerging ﬁeld with interesting perspectives and possibilities. Although there is an economic rationale behind it (lowering the cost of in situ observation networks), it encloses the possibility of using ICT in the creation of a relation between public authorities and citizens that can produce a valuable return for citizens.